Al-Iʽlāl fī Sūrah al-Furqān - Achmad Shofyan Baihaqi (JILSA (Jurnal Ilmu Linguistik dan Sastra Arab), 2022)
In this thesis there is an explanation of i'lal, its types and their rules, from various types and rules the author uses a tool to analyze the Surah al-Furqān. The problems raised in this study are, 1) What are the verses that indicate i'lal in Surah al-Furqān? 2) what are the types of i'lal in surah al-Furqān? The approach in this study is the sharf discipline, especially in the discussion i'lāl While the method used is descriptive qualitative method. Qualitative is research that discusses, analyzes and classifies the i'lāl contained in the letter al-Furqān. Descriptive is to describe the results of these studies systematically about i'lāl in the letter al-Furqān. i'lāl is a change that occurs in the letters 'illat (alif, wawu, ya') and additional letters (hamzah), the changes are sometimes moved, discarded, replaced, and distributed. While the letter al-Furqān is a letter that is at number 25 out of a total of 114 ayah. As for the results of this study, 45 verses have been found that contain I'lāl. And in these verses 65 data were found which the writer then classified into 11 sections.